Enhancing Conceptual Understanding in Geometry of Curved Solids: A Constructivist Philosophy Approach through Interactive E-Module for Secondary School Students - Santosa, Yoga Tegar; Hastuti, Windi; Ismiyati, Ismiyati; Ferdianto, Juli; Kholid, Muhammad Noor (Jurnal VARIDIKA, 2026)
Conceptual understanding is a crucial aspect of mathematics learning. However, in practice, students’ mathematical conceptual understanding often tends to be low. One potential solution is the implementation of an interactive e-module grounded in constructivist philosophy to facilitate deeper understanding of mathematical concepts. This study aims to examine the influence of using a constructivist-philosophy-based interactive e-module on students’ conceptual understanding in geometry of curved solids at the secondary school level. The research employed a quantitative quasi-experimental approach with a pretest–posttest non-equivalent control group design. The participants consisted of 62 ninth-grade students from a public junior secondary school in Boyolali Regency, Indonesia, who were divided into experimental and control groups. Data were collected using a conceptual understanding test that was validated and demonstrated good reliability (Cronbach’s α = 0.82). Data analysis was conducted using descriptive and inferential statistics. The Mann–Whitney U test revealed a significant difference in post-test scores between the experimental and control groups (p < 0.001), with the experimental group achieving a higher median score (75) than the control group (55.5). The effect size analysis indicated a strong practical effect (r = 0.77), suggesting that the observed difference was not only statistically significant but also educationally meaningful. These findings indicate that the constructivist-philosophy-based interactive e-module was effective in supporting the enhancement of students’ conceptual understanding of geometry of curved solids. Furthermore, students who learned the material using the e-module demonstrated significantly better conceptual understanding than those who did not. These findings can serve as a reference for teachers in selecting appropriate digital learning media, while also contributing to the development of mathematics learning innovations oriented towards constructivism.